Screening of Colombian soybean genotypes for Agrobacterium mediated genetic transformation conferring tolerance to Glyphosate - Alejandro Chaparro Giraldo; Adriana Carolina Rojas; Silvio Alejandro Lopez Pazos (Agronomía Colombiana, 2018)
Soybean is a very important crop worldwide due to its multiple uses as raw material for industry and to its high nutritional value. Colombia consumes a large amount of imported soybean because domestic production does not supply demand. There are soybean varieties adapted to the environmental conditions in the Colombian territory, but none of them have been enhanced by genetic engineering to confer competitive advantages compared to imported product. In this research, the Colombian soybean varieties SK7, P29 and Soyica P34 ability to be genetically transformed by Agrobacterium tumefaciens strains AGL0 and EHA105 using a Glyphosate tolerance cassette was tested. It was found that SK7 variety presented a better regeneration performance from the cotyledonary node,and also had the highest transformation frequency with AGL0 strain. The P29 variety was also transformed, but a lower efficiency was registered. It was not possible to transform Soyica P34 variety under the established parameters. This research is an advance towards the construction of a platform to enhance the generic transgenic crops in Colombia.